IT/IS Strategic Planning pada Sektor Edukasi Studi Kasus Universitas Bakrie (LPPM STT Terpadu Nurul Fikri, 2017)
The using of Information Technology in higher education institutions have become the success key of teaching & learning process, research and academic administration. Universitas bakrie has been established for ten years. Over time the deployment of IS/IT at the Universitas Bakrie have been progressing. But in 3 years before, it appears that the plan is not entirely referring to vision, mission and process business of Universitas Bakrie. Therefore in this research aims to discussing about the IS/IT strategic planning at Unversitas Bakrie. The design process is based to a model IS/IT strategic planning (Ward & Peppard,2002) where the steps consisting of analysis of the external and internal environment Universitas Bakrie and analysis of the external and internal environment IS/IT Universitas Bakrie. After the analysis is done, IS/IT strategic planning, IS/IT management planning and the implementation of the design IS/IT planning in 3 years. Finally the result of this research is expected to give a description of IS/IT strategic planning to be used as reference in IS/IT planning annual in Universitas Bakrie. Key words : higher education, strategic plan, IS/IT strategic Plan